COMPARATIVE STUDIES OF THE EDIBLE FILM BASED ON LOW PECTIN METHOXYL WITH GLYCEROL AND SORBITOL PLASTICIZERS - Darni, Yuli; Utami, Herti; Septiana, Rina; Fitriana, Rizka Aidila (Universitas Negeri Semarang, 2017)
This study aims to compare the characteristics of mechanical and water vapor permeability of edible film based on low pectin methoxyl from cocoa skin with glycerol and sorbitol as plasticizer. In the research also added CaCO3 filler with the weight variation of 0; 0.2; and 0.4 gr. Pectin from cocoa peel was isolated by extraction use ammonium oxalic at a temperature of 85oC, pH of 3.6 for 60 minutes. An edible film synthesized at a temperature of 85oC to the agitation time of 50 minutes. 200 mesh of pectin used with the variation of glycerol and sorbitol plasticizer concentration are 1, 2 and 3% in volume. Edible films produced were dried at a temperature of 55oC for 6 hours. The results of the study obtained in 0.2 gr CaCO3 concentration and 1% glycerol of edible films has a tensile strength of 0.3267 mpa, percent elongation of 12.84%, modulus young of 2.5441 mpa, and the water vapor permeability of 4.1676 g/m2.day. While in 0.4 gr CaCO3 concentration and 1% sorbitol of edible films has a tensile strength of 6.511 mpa, percent elongation of 2.419%, modulus young of 269.119 mpa, and the water vapor permeability of 5.583 g/m2.day. Based on percent elongation characteristics, glycerol plasticizer made higher elasticity than sorbitol plasticizer. While the addition of filler able to increase tensile strength two times larger than without filler.